Injectable anesthesia and effects of analgesics on the immune response in Jamaican fruit bats - Pollak, Marissa, author; Kendall, Lon, advisor; Schountz, Tony, committee member; Boscan, Pedro, committee member (Colorado State University. Libraries, 2025)
Injectable anesthesia and immunomodulatory effects of buprenorphine and meloxicam in Jamaican fruit bats (Artibeus jamaicensis) (JFBs) have not been studied to date. Testing injectable anesthetic protocols in JFBs would allow for potential alternatives to isoflurane anesthesia which is relied upon in the field and in laboratory settings, but requires special equipment and can be difficult to manage in the field. Injectable anesthetic protocols in bats have been studied in limited capacity yet are valuable due to minimal equipment needs and the ability to induce multiple animals in succession. Four injectable anesthetic protocols (n=6) were compared with isoflurane inhalant anesthesia (control, n=5) in JFBs. Ketamine (K), alfaxalone (A), butorphanol (B), and nalbuphine (N), were each combined with dexmedetomidine (DX) and delivered intraperitoneally, followed by subsequent reversal with atipamezole. KDX and ADX induced anesthesia in 5 out of 6 bats, while NDX and BDX only induced mild to moderate sedation in all bats. All groups except for KDX resulted in return to flight within 60 minutes of injection. In summary, KDX and ADX induced anesthesia in the majority of bats tested and are viable alternatives compared to isoflurane alone. As KDX resulted in a prolonged return to flight time, it is not ideal for use in the field where timely recovery is needed to ensure the safety of bats. Bats are frequently used as a model to study emerging infectious diseases and bat immune responses. These studies may result in clinical signs, such as flu-like symptoms, in the bats. Minimizing pain and distress is a priority in laboratory animal medicine and is necessary to remain in compliance with regulations including the Guide for Care and Use of Laboratory Animals and the Animal Welfare Act. Opioids and non-steroidal anti-inflammatory drugs (NSAIDs) can be used to mitigate the potential pain and distress associated with infectious agents. Here we aim to understand how buprenorphine HCl (BUP), an opioid and meloxicam (MEL), an NSAID, affect the immune response in JFBs. Three male and three female bats in each group were immunized subcutaneously with keyhole limpet hemocyanin (KLH) with complete Freund's adjuvant on day 1. Immediately prior to immunization, bats were bled for baseline IgG determination. Subcutaneous doses of meloxicam (MEL) at 5 mg/kg, buprenorphine (BUP) at 1 mg/kg, or 0.15 mL of saline (SAL) were given daily for 21 days. On day 21, bats were given a subsequent immunization with KLH and incomplete Freund's adjuvant. On day 28 bats were euthanized and blood was collected to assess IgG responses in the serum and spleens were isolated to assess gene expression responses in KLH stimulated splenocytes. Antibody response to KLH was measured by ELISA and gene expression profiling was evaluated by RT-qPCR. There were no antibodies detected prior to immunization in any group. After immunization and treatments, all groups had elevated antibody responses. There were no statistical differences in the antibody responses of bats treated with either BUP or MEL compared to SAL treated bats. The only statistically significant difference in gene expression was decreased IL-13 expression in BUP treated bats compared to SAL treated bats. Overall, these results suggest that the use of BUP or MEL will have minimal impact on the bat immune response.